Evaluasi Penggunaan dan Outcome Terapi Obat Antinyeri pada Pasien Diabetik Neuropati di RS PKU Muhammadiyah Surakarta - Rahayu Putri Priyanda; Vivin Marwitari Rohmana; Rizka Wahyu Syahputra (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Diabetic neuropathy is a type of neuropathic pain commonly found in patients with diabetes, resulting from damage to the central or peripheral nervous system. Neuropathic pain is one of the most frequent and distressing symptoms experienced by patients with diabetic peripheral neuropathy, affecting approximately 16% to 26% of patients. Neuropathic pain can significantly impact daily activities, self-care ability, work productivity, and sleep quality (Rivani et al., 2024). This study aimed to analyze the patterns of analgesic therapy use in patients with diabetic neuropathy and to evaluate the effectiveness of such therapy in reducing neuropathic pain levels. This study employed a retrospective observational design, using medical records data from January to December 2024. Data collected included patient characteristics, types and doses of analgesic drugs, and clinical outcomes based on pain improvement. Descriptive analysis and Chi-Square tests were performed. A total of 72 samples meeting the inclusion criteria were obtained. The evaluation of the use and outcomes of analgesic therapy in patients with diabetic neuropathy at PKU Muhammadiyah Hospital Surakarta revealed that the effectiveness of therapy was assessed based on patient outcomes after treatment. Most patients showed improvement in pain conditions, with Gabapentin demonstrating the highest effectiveness in reducing neuropathic pain. The Chi-Square test analysis on the relationship between the type of analgesic drug combination and the patient’s pain level after therapy yielded a significance value of 0.005. Since the significance value was <0.05, it can be concluded that there is a statistically significant relationship between the type of drug administered and the patient’s pain level after undergoing therapy.